Assessment of the Impact of the Uranium Industry on the Environment and Population - Lyashenko, Vasyl; Stus, Viktor; Kyselov, Yuriy; Lisovyi, Ivan (Revista minelor (Bucharest, Romania : 1990), 2025)
The paper provides an assessment of the impact of the uranium industry on the state of the environment and the population based on the development and implementation of engineering solutions and measures to reduce gamma radiation and radon concentration in the premises, the implementation of environmental and social rehabilitation of the contaminated territory, residential buildings, objects social sphere and the population living in the zone of influence of uranium facilities. The specified measures are aimed at improving the environmental safety of the environment and the population in order to minimize the negative impact of radiation and other factors. Used radiometric methods (measurement of the exposure dose and intensity of γ-radiation, measurement of the radioactivity of γ- and β-radiation, measurement of the power of the exposure dose of γ-radiation, determination of the power of the absorbed dose of γ-radiation in air, analysis of natural radionuclides (PRN); statistical and mathematical research methods using an integrated system approach Radioecological studies included: measurement of the exposure dose rate (PED) of γ-radiation by the network 100 x 10 m (walking survey) in the area of 40 km2, soil sampling for radium and uranium content, determination of radon concentration in residential premises specialists of various bodies of state power and local self-government in solving the above-mentioned tasks, for the regions located in the zone impact of mining and beneficiation plants for mining and primary processing of uranium ores. It was established that exceeding the normative level of the equivalent equilibrium concentration of radon of 50 Bq/m3 in individual rooms is caused by its release from the underground space and input channels of external heat and water supply networks, internal channels of distribution of heat networks. It has been proven that filling the heat network channel from the outside of the building with a layer of clay to a depth of 1 m and sealing it, sealing the entry of heat and water networks through the foundation of the building and concreting the pit reduce the volumetric activity of radon in the room by 5-6 times. The so far rare experience of increasing radiation and social protection of the population of the city of Zhovti Vody, Ukraine, which has been living in the zone of influence of uranium industry facilities for more than 70 years, is presented. It is proposed to continue research and provide funds (at the expense of enterprises, local and central state authorities) for conducting scientific substantiation and developing preventive measures to minimize the negative effects on human health from the action of heavy metals and radiation factors, taking into account the peculiarities of their combined impact on the population and workers of the uranium mining and mining and metallurgical industry.